Determinants of Resistance to Changes in Hospital Program Implementation - Rusmawati, Aprin; Wardani, Ratna; Fajriah, Asruria Sani (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Organizational change is the embodiment of changing organizational environments, structures, cultures, technologies, or people. Changes are planned to make the organization more effective and efficient, but there is still resistance from members of the organization. Negative reactions arise because changes provide pressure, stress, and uncertainty for employees. The goal in the study was to analyze employees' perceptions of commitment, readiness, and resistance during times of change to the implementation of the